Model of motivational competence: creation of students’ motivation, assessment, and research - Satka, Fjoralba; Garneva, Emilia (Frontiers in Education, 2024)
The basic finding uniting the researchers is that motivation is the weakest educational component, which prompted us to create and suggest a practical model of motivational competence. The project is based on the researchers’ descriptions of students’ motivational leading variables. Our main finding is lack of a value system and moral virtues in the foundation of motivation. The constructive components of the model cognition, cogitation, and skills were built on that basis. The main functional approaches in the study with the model are communication, feedback, and critical thinking. The model aims: (1) to direct teachers in creating and maintaining students’ motivation through motivational competence based on human values and virtues and (2) to strongly recommend that educational policies must pinpoint a value system and moral criteria for schools and universities so that educators can rigorously develop them in students through motivation. The contributions of the model are: (1) it is based on the crucial need for a strong value system and moral virtues in the foundation of students’ motivation and behavior; (2) it is bidirectional—developing students’ motivational competence, in parallel it increases teachers’ motivational competencies; (3) it argues that motivational competence must be the professional imperative leading to the curriculum purposes of teaching–learning process on the foundation of competence, high spiritual qualities, and morality.